2014
DOI: 10.1161/circulationaha.113.007911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Implantation of a Centrifugal Flow Left Ventricular Assist Device and Concurrent Cardiac Valve Procedures

Abstract: Background— Cardiac valve procedures are commonly performed concurrently during implantation of left ventricular assist devices, but the added procedural risk has not been studied in detail. Methods and Results— Data from patients receiving the HeartWare Ventricular Assist Device in the ADVANCE bridge to transplant (BTT) trial and continued access protocol were reviewed. Of 382 consecutive patients who completed follow-up between August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 21 publications
3
30
1
1
Order By: Relevance
“…The authors found that gastrointestinal bleeding was present in almost half of the patients and they identified female gender and age as the most significant risk factors. The authors suggest that specific anticoagulation [59]. Similar findings specifically addressing concomitant tricuspid valve surgery were reported by Fujita et al [60] and Brewer et al [61].…”
Section: Tricuspid Valve Surgerysupporting
confidence: 75%
“…The authors found that gastrointestinal bleeding was present in almost half of the patients and they identified female gender and age as the most significant risk factors. The authors suggest that specific anticoagulation [59]. Similar findings specifically addressing concomitant tricuspid valve surgery were reported by Fujita et al [60] and Brewer et al [61].…”
Section: Tricuspid Valve Surgerysupporting
confidence: 75%
“…Despite significant differences between groups, patients in the LVAD + TVP group had a comparable long-term survival and probability of device-related adverse events. Results differ from outcomes reported by John et al 8 for the HMII investigators, or results observed for the HVAD by Milano et al 9 A population of 37 patients implanted in a single center (Mayo Clinic) had concomitant tricuspid valve procedures (32 repairs, five replacements) for severe TR. The effects of a tricuspid valve procedure on TR and right ventricular remodeling were assessed comparing echocardiographic findings at baseline and 30 days after LVAD implantation.…”
Section: Tricuspid Insufficiencycontrasting
confidence: 58%
“…8,9 As reported, we found that LVAD + TVP is the most common CP procedure performed at the time of LVAD implantation (42%). In our analysis, several important differences exist between groups with or without a CP.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations